2014
DOI: 10.1371/journal.pone.0095557
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence of Expressed Fungal Secretory Peroxidases in Forest Soils

Abstract: Fungal secretory peroxidases mediate fundamental ecological functions in the conversion and degradation of plant biomass. Many of these enzymes have strong oxidizing activities towards aromatic compounds and are involved in the degradation of plant cell wall (lignin) and humus. They comprise three major groups: class II peroxidases (including lignin peroxidase, manganese peroxidase, versatile peroxidase and generic peroxidase), dye-decolorizing peroxidases, and heme-thiolate peroxidases (e.g. unspecific/aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 52 publications
7
69
0
Order By: Relevance
“…In terms of the sources of enzymes, LiPs occur in members of the Polyporales and Corticiales and VPs stem from the Agaricales and Polyporales, whereas MnPs occur in at least four orders, the Polyporales, Corticiales, Agaricales, and Corticiales [53,54], which explains why MnPs are prevalent in nature and also indicates that MnPs may have originated relatively early in the evolutionary history of class II fungal heme peroxidases. Moreover, this result supports the findings of Kellner et al [3], which showed that the widespread occurrence of this peroxidase type is of a strong biological significance for the conversion and degradation of plant biomass.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the sources of enzymes, LiPs occur in members of the Polyporales and Corticiales and VPs stem from the Agaricales and Polyporales, whereas MnPs occur in at least four orders, the Polyporales, Corticiales, Agaricales, and Corticiales [53,54], which explains why MnPs are prevalent in nature and also indicates that MnPs may have originated relatively early in the evolutionary history of class II fungal heme peroxidases. Moreover, this result supports the findings of Kellner et al [3], which showed that the widespread occurrence of this peroxidase type is of a strong biological significance for the conversion and degradation of plant biomass.…”
Section: Discussionsupporting
confidence: 92%
“…It must be considered that the GenP activities measured here represent sum activities that rely on several fungal peroxidases (Kellner et al 2014), among which only LiP and VP are truly ligninolytic (Hofrichter et al 2010;Ruiz-Dueñas and Martínez 2009). Consequently, the relation of LiP and VP to water-soluble lignin fragments could be masked/corrupted by activities of GP, UPO and DyP (Hofrichter et al 2010;Liers et al 2011).…”
Section: Lacc Genp and Mnp Activities Are Crucial For Lignin Conversmentioning
confidence: 99%
“…The GenP activity stands for the sum activity of a genetically diverse set of fungal peroxidases that can include LiP, VP, GP, UPO and DyP in the absence of Mn 2? , which is why the GenP activity has also been described as activity of manganese-independent peroxidases (MiP; Kellner et al 2014). All measurements were taken in duplicate and were repeated when the absorbance increase in the two measurements was strongly deviating.…”
Section: Activities Of Lacc and Peroxidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity is prone to produce humic-type SOM and lignin degradation. In fact, the abundance of unspecific aromatic compounds could also have an origin in the fungal alteration of plant lignins (Kellner et al, 2014).…”
Section: Scenariomentioning
confidence: 99%